Root canal working length determination using Cone-Beam Computed Tomography - Đeri Aleksandra; Kuzmanović-Radman Irena; Čavić Miloš; Vujaković Ilija; Arbutina Adriana; Uzelac Teodora; Uzelac Marko; Jović Dragana (Serbian Medical Society - Dental Section, Belgrade, 2019)
Introduction Cone-Beam Computed Tomography (CBCT) represents unique supporting diagnostic tool in all areas of dentistry as well as endodontics. One of the uses in endodontics is determining working length of the root canals-odontometry. The aim of this paper was to test the efficacy of CBCT application in determining working length of root canals. Methods Forty-three extracted human teeth were placed in three wax models shaped as a horseshoe. Preoperatively, CBCT model scanning (voxel size: 0.2 mm) was performed. Access cavities were prepared and working length determined by introducing expanders #08 into the root canal until the apical foramen. The length was measured using a micrometer odontometer. The CBCT working length was simply measured by following the line between the apical foramen and the selected reference point. Two experienced operators performed all measurements, independently. The t-test was used to compare the obtained values. Results CBCT measurements showed small deviation from manual measurements. The mean value of the absolute difference between CBCT measurements and manual measurements was 0.39 mm (0.25-0.74 mm). The results of the t test (t = 0.311; p = 0.757) showed that there was no statistically significant difference between the odontometry performed by the endodontic instrument and odontometry performed using CBCT. Conclusion the CBCT measurement is reliable method for determining working length of root canals. In 94.29% of examined teeth, discrepancies less than 1 mm were found, which was not of clinical significance.